Complications of Paediatric Ventriculoperitoneal (VP) Shunt: Experience in A Tertiary Care Hospital - Paul, Swapan Kumar; Islam, Rakibul; Ghosh, Paritosh Kumar; Biswas, Prosanto Kumar; Hossain, Delwar; Rashid, Md Aminur (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: Ventricloperitoneal (VP) shunt is the most commonly used shunt procedure in children because of the capacity of the peritoneum to resorb fluid like Cerebrospinal fluid (CSF). Primary and subsequent peritoneal catheter placement is relatively easy procedure to be done. VP shunt procedures are associated with varieties of complications. Methods: A prospective study was done from July 2017 to June 2021 in Faculty of Paediatric Surgery, Bangladesh Shishu Hospital & Institute. A total number of cases underwent VP shunt surgery were 192. We had analyzed 82(42.71%) patients of VP shunt surgery who had various shunt related complications and analyzed the predisposing risk factors and spectrum of complications. Results: The mean age was 16±14 months and median age was11.75 months. Out of 82 patients 56 (68.29%) were male and 26(31.71%) were female. Seventy (85.37%) patients had single complication and 12(14.63%) had more than 1 complications. Twenty four (29.27%) patients had infective complication and 58(70.73%) had mechanical complication. Infective complications (24, 29.27%) include shunt tract abscess (41.66%), CSF leak (16.67%) exposure of shunt tube through anus (16.67%), wound infection (16.67%). Mechanical complications were present in 58(70.73%) cases and 40(48.78%) had ventricular end malformation, 24(29.27%) peritoneal end and 18(21.95%) had both end malformation. Conclusion: With this prospective study of complications of VP shunt, age at initial shunt surgery, insertion and important patient-related predictors of shunt failure. The different predominant etiological factors the interval between the age of initial shunt placement and onset of complications were the most responsible for early and late shunt failure were infective and mechanical complications respectively. DS (Child) H J 2021; 37(2): 129-134